Green synthesized 3D coconut shell biochar/polyethylene glycol composite as thermal energy storage material - Kalidasan, B.; Pandey, A. K.; Saidur, R.; Aljafari, Belqasem; Yadav, Aman; Samykano, Mahendran (Elsevier, 2023)
Developing stable, economic, safer and carbon-based nanoparticles from agro solid waste facilitates a new dimension of advancement for eco-friendly nanomaterials in competition to existing nanoparticles. Herewith, a three dimensional highly porous honeycomb structured carbon-based coconut shell (CS) nanoparticle is prepared through green synthesis technique using tube furnace to energies organic phase change material (PCM). CS nanoparticle synthesis using a green approach is incorporated with polyethylene glycol (PEG) using a two-step technique to develop PEG/CS nanocomposite PCM. Thermophysical features of the nanocomposites are characterized using transient hot bridge (ThB), differential scanning calorimeter (DSC) and thermogravimetric analysis (TGA), whereas optical property and chemical stability is evaluated using UV–Vis and FTIR spectrometers. Resulting nanocomposite demonstrates higher thermal conductivity by 114.5 % (improved from 0.24 W/m⋅K to 0.515 W/m⋅K). Energy storage enthalpy increased from 141.2 J/g to 150.1 J/g with 1.0 % weight fraction of CS nanoparticles. Optical absorbance of the nanocomposite is improved by 2.14 times compared to base PCM. The developed nanocomposite samples exhibit extreme thermal stability up to 215 °C. The 3D porous structure of CS nanoparticles shows better contact area with PEG, causing low interfacial thermal resistance for improved thermal network channels and pathways for extra heat transfer and phonon propagation.